Social and solidarity economy and the future of work - Borzaga, Carlo; Salvatori, Gianluca; Bodini, Riccardo (Geneva, 2017)
"This publication presents the main theoretical arguments and empirical evidence on the features and role of social and solidarity economy (SSE) organizations, specifically on its potential to create and preserve decent work. The publication also underlines the SSE’s capacity to create jobs in emerging sectors, for example in the silver economy, and to contribute to the formalization of the informal economy. Lastly, the policy implications of these various changes, and how they can support the growth and development of SSE in the future of work are addressed."